Estetyzowanie wulgaryzmów - Kita, Małgorzata (Stylistyka, 2020)
The article concerns vulgar words and vulgarization of utterances in contemporary Polish public sphere. Aestheticization of vulgar words does not only mean a nice use of “bad words” or creative and individual approach towards them. It also means their inclusion in the sphere of culture, despite many controversies about using them as fully viable means of artistic expression and freedom. Much attention is given to the presence of vulgar words in artistic undertakings. The author concentrates on the strictness of the recipients’ attitudes towards vulgar words. On one hand, the users of vulgar words are stigmatized, on the other, the use of these words is socially accepted as elements of creative activity. Numerous examples of introducing vulgar words into cultural texts, though very controversial, show the importance of such artistic acts. The scientific per- spective used in the article is cultural linguistics.